A survey of descriptions of immature instars of mites during the last three years - Liu, Jian-Feng; Zhang, Zhi-Qiang (Zootaxa, 2018)
Immature instars of mites can provide valuable information for understanding mite taxonomy and evolution. However, most taxonomists described only adults and rarely did they also describe immature stages and the ontogenetic sequence. For example, only about 8% of the known oribatid mites (excluding Astigmata) have one or more juvenile instars described (Norton & Ermilov 2014). Since then we noted rapid increase of papers on the ontogeny of oribatid mites as well as other mites in Systematic and Applied Acarology during our editing and production process. The purpose of this paper is to provide a survey of descriptions of immature instars of mites during the last three years (2015–2017). We follow our previous methods in sampling most important journals in mite systematics (Liu et al. 2013; Liu & Zhang 2016; Li & Zhang 2016; Wei & Zhang 2016; Liu et al. 2017), while expanding the scope further to include more journals that publish a significant amount of mite taxonomic papers.